Development of an improved vaccine for contagious bovine pleuropneumonia: An African perspective on challenges and proposed actions - Jores, Joerg; Mariner, Jeffrey C.; Naessens, Jan (Springer, 2013)
Contagious bovine pleuropneumonia (CBPP) caused by Mycoplasma mycoides subsp. mycoides (Mmm) is an economically very important cattle disease in sub-Saharan Africa. CBPP impacts animal health and poverty of livestock-dependent people through decreased animal productivity, reduced food supply, and the cost of control measures. CBPP is a barrier to trade in many African countries and this reduces the value of livestock and the income of many value chain stakeholders. The presence of CBPP also poses a constant threat to CBPPfree countries and creates costs in terms of the measures necessary to ensure the exclusion of disease. This opinion focuses on the biomedical research needed to foster the development of better control measures for CBPP. We suggest that different vaccine development approaches are followed in parallel. Basic immunology studies and systematic OMICs studies will be necessary in order to identify the protective arms of immunity and to shed more light on the pathogenicity mechanisms in CBPP. Moreover a robust challenge model and a close collaboration with African research units will be crucial to foster and implement a new vaccine for the progressive control of this cattle plague.